Health Behaviors and Quality of Life of Cancer Survivors in Massachusetts, 2006: Data Use for Comprehensive Cancer Control - Temeika L. Fairley, PhD; Helen Hawk, PhD; Snaltze Pierre, MPH (Centers for Disease Control and Prevention, 2010)
IntroductionNearly 12 million cancer survivors are living in the United States. Few state-based studies have examined the health status and health-related quality of life (HRQOL) of this growing population. The objective of this study was to use Massachusetts Behavioral Risk Factor Surveillance System (BRFSS) data to describe cancer survivors' demographics, health behaviors, quality of life, use of preventive care services, and influenza vaccination rates.MethodsThe demographic characteristics of cancer survivors and respondents without cancer were estimated on the basis of responses to questions in the 2006 Massachusetts BRFSS. We used multivariate logistic regression to compare health behaviors, comorbidities, quality of life, and cancer screening and influenza vaccination rates for cancer survivors compared with respondents who did not have cancer.ResultsCancer survivors and respondents who did not have cancer had similar rates of health behavioral risk factors including smoking, obesity, and physical activity. Rates of chronic disease (eg, heart disease, asthma) and disability were higher among cancer survivors. Cancer survivors reported higher rates of influenza vaccination and breast, colorectal, and cervical cancer screening than did respondents who did not have cancer. Survivors' self-reported health status and HRQOL (physical and mental health) improved as length of survivorship increased.ConclusionThis state-based survey allowed Massachusetts to assess health-related issues for resident cancer survivors. These findings will help state-based public health planners develop interventions to address the long-term physical and psychosocial consequences of cancer diagnosis and treatment.